2005
DOI: 10.1097/01.ccm.0000185645.84802.73
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of red blood cell transfusions in a pediatric critical care unit: A prospective, descriptive epidemiological study*

Abstract: A significant proportion of critically ill children receive at least one red blood cell transfusion during their PICU stay. Presence of anemia, cardiac disease, severe critical illness, and multiple organ dysfunction syndrome are the most significant determinants of red blood cell transfusions in PICU.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
55
1
4

Year Published

2007
2007
2016
2016

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 87 publications
(70 citation statements)
references
References 32 publications
6
55
1
4
Order By: Relevance
“…However, our study was methodologically different compared with the study by Goodman et al [4]. Because patients with a pre-transfusion Hb greater than 9 g/dl are also (often) transfused, we included all patients irrespective of the pre-transfusion Hb value [3,17]. With this inclusion method we not only support the observations by Goodman et al [4] but also observed an even stronger association, adding more strength to our study.…”
Section: Discussionsupporting
confidence: 74%
See 3 more Smart Citations
“…However, our study was methodologically different compared with the study by Goodman et al [4]. Because patients with a pre-transfusion Hb greater than 9 g/dl are also (often) transfused, we included all patients irrespective of the pre-transfusion Hb value [3,17]. With this inclusion method we not only support the observations by Goodman et al [4] but also observed an even stronger association, adding more strength to our study.…”
Section: Discussionsupporting
confidence: 74%
“…In our study we found that 13.4% of the patients had a Hb below 9.7 g/dl. Also, our transfusion rate is in accordance with previously reported numbers by others [3]. Based upon this study we advocate further investigations aimed at defining a suitable and safe threshold value for Hb used in the decision as to when to transfuse a critically ill child, stratifying for age, disease severity, and co-morbidities.…”
Section: Discussionsupporting
confidence: 72%
See 2 more Smart Citations
“…RBCTs have been recognized to pose risks associated with storage and in relation to the immunomodulatory effects that occur in almost all recipients; this underlines a possible association between RBCT and higher mortality and nosocomial infection rates. [2][3][4] Recognizing these risks has resulted in a more critical approach to the benefits associated with RBCT. The underlying mechanisms of immune response modulation by RBCT may include biological response modifiers of white blood cells, impaired T cell and natural killer cell activity, and defects in antigen presentation.…”
Section: Introductionmentioning
confidence: 99%